THE IMPORTANCE OF UZBEKISTAN POTTERY AS AN APPLIED ART IN THE YEARS OF INDEPENDENCE - Ruziyev Nuriddin Mukhamadalievich (Journals Park Publishing, 2025)
This article examines the stages of development of Uzbek national applied arts since independence. It presents work on applied arts in pottery, as well as information on traditions and values, schools, and pottery centers in our country.
Keywords: Applied arts, pottery, clay, master, spool, potter's wheel, school, center, tradition, artistic, art, student.